Bleeding Ectopic Varices as the First Manifestation of Portal Hypertension - Brij Sharma; Sujeet Raina; Rajesh Sharma (Case Reports in Hepatology)
Ectopic varices are defined as dilated portosystemic collateral veins in locations other than the gastroesophageal region. We present a case of recurrent upper gastrointestinal bleeding as the first manifestation of portal hypertension. We diagnosed ectopic duodenal varices without gastroesophageal varices on upper GI endoscopy and extrahepatic portal venous obstruction (EHPVO) on CT angiography and managed this case.